Intracardiac thrombus in Behçet's disease - I. Ben Ghorbel; N. Belfeki; M.H. Houman (PAGEPress Publications, 2016)
Behçet's disease (BD) is a multisystem inflammatory disorder. Intracardiac thrombus (ICT) formation is an uncommon but important complication of BD. Of the cases of Behçet's disease, we selected those with ICT. All patients fulfilled the diagnostic criteria of the International Study Group of Behçet's disease. The ICT in each case was confirmed by ultrasonography, computed tomography and MRI. Clinical features and laboratory parameters were determined. Among our 518 patients with BD, 8 were diagnosed as having intracardiac thrombus (ICT). All were male; the mean age at the time of the ICT diagnosis was 30.8 years. The main presenting symptoms were hemoptysis, chest pain, and dyspnea. It was associated with pulmonary artery aneurysm and vena cava thrombosis in 3 cases each, pulmonary embolism, and lower limbs deep venous thrombosis in 1 case each. The coexistence of other cardiac complications was as follows: pericarditis in 2 cases, myocarditis, endomyocardial fibrosis, and coronary arteritis with consequent myocardial infarction in one case each. In all cases, echocardiography was sufficient to reach the diagnosis. Chest computed tomography performed in all cases led to the diagnosis of associated pulmonary vasculo-Behçet lesions in 4 cases. All patients received colchicine, anticoagulation, and corticosteroids. Seven patients were on immunosuppressant agents (2 patients received azathioprine and 5 cyclophosphamide). Clinical remission with ICT resolution was observed in 5 cases. Combined immunosuppressive therapy with prednisone and cyclophosphamide might be needed to treat ICT due to BD.